Effects of destruxin A on hemocytes of the domestic silkworm, Bombyx mori - Yin, Fei; Hu, Lina; Li, Zhenyu; Yang, Xiangbing; Kendra, Paul E.; Hu, Qiongbo (Frontiers in Microbiology, 2023)
Destruxin A (DA) is a mycotoxin isolated from the entomopathogenic fungus Metarhizium anisopliae which has demonstrated inhibitory activity against various insect species. However, the mechanism of inhibition on target sites in insects remains unknown. In this research, the dose-response relationship between DA and morphological changes in body tissues and organs of domestic silkworm, Bombyx mori, were investigated by histopathological methods to identify the target sites that responded to DA. The results showed that responses of individual tissues and organs varied with DA dosage and treatment time. At low doses (i.e., 0.01μg/g), the hemocytes were the most sensitive to DA with morphological changes apparent at 6 h after treatment. However, the muscle cells, fat body, and Malpighian tubules were unaltered. At higher doses (i.e., > 0.1μg/g), morphological changes were observed in muscle cells, fat body, and Malpighian tubules at 24 h after treatment. The results indicated that DA can be an immunosuppressant by damaging host cells like hemocytes, and at higher doses may potentially impact other physiological processes, including muscle function, metabolism, and excretion. The information presented in the current study will facilitate development of mycopesticides and novel immunosuppressants.